2019
DOI: 10.26773/smj.191012
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Athletic Performance through Nutrition Knowledge and Practice: A Cross-Sectional Study among Young Team Athletes

Abstract: The present study was conducted to assess the nutrition knowledge, practice, and status and to identify the nutritional and body composition factors predicting athletes' performance. Young team athletes including 40 footballers and 50 hockey players were recruited in this study (age 16.48±1.5) to assess the nutrition knowledge (NK), nutrition practice (NP), and 24-hour dietary recall using a semi-structured questionnaire. Physical characteristics, including height, weight and body mass index (BMI), along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(39 reference statements)
2
6
0
4
Order By: Relevance
“…As stated in previous research [2], the key for the development of this journal is 2017, when the journal was indexed in the "Scopus" database, since when the citation has been on the rise. A good indicator of the progressive growth of this journal are the scientific papers of eminent researchers published during 2019 [24,25,26,27,28,29,30,31,32,33]. It is important to emphasize that the journal has maintained constant growth, which is confirmed by the findings of this study and there is a real possibility that it will enter the most prestigious database "Web of Science".…”
Section: Discussionsupporting
confidence: 70%
“…As stated in previous research [2], the key for the development of this journal is 2017, when the journal was indexed in the "Scopus" database, since when the citation has been on the rise. A good indicator of the progressive growth of this journal are the scientific papers of eminent researchers published during 2019 [24,25,26,27,28,29,30,31,32,33]. It is important to emphasize that the journal has maintained constant growth, which is confirmed by the findings of this study and there is a real possibility that it will enter the most prestigious database "Web of Science".…”
Section: Discussionsupporting
confidence: 70%
“…Oxygen consumption significantly increased 7.5% from preseason to postseason and there was an increase of Although the findings revealed a decrease in total workload between the season halves, previous data have shown basketball athletes spend on average nearly 30% of total game duration at intensities $85% HR max (24), which may account for why no change in HR zone5 occurred in the second half of the season. There was an increase in the number of games played in the second half of the season ( 22) compared with the first half (8) and it should be expressed that practice sessions are more vigorous in the first half of the season to prepare for game demands. Furthermore, multiple studies have shown engagement in high-aerobic-intensity interval training (i.e., 90-95% HR max ) has a significant effect on improving V Ȯ2peak , even in higher-level athletes (6,12,13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Maximal oxygen consumption is a measure of aerobic capacity and is likely altered throughout a competitive season because of numerous factors such as the duration, frequency, and intensity of games and practices throughout a season (18). Other factors may contribute to increases or decreases in aerobic capacity such as injuries, playing time, poor nutrition, and fatigue (5,8,25). Previous research regarding professional women's basketball athletes found that the high-minute athletes had a significantly higher V Ȯ2max than low-minute athletes (29).…”
Section: Introductionmentioning
confidence: 99%
“…Another studywhich aimed to determine different endurance sports types and athletes' nutritional habitsfound that cyclists' nutritional habits were better than others (Baranauskas et al, 2015). In another study that aimed to evaluate the effects of nutritional habits on physical performance in athletes from different branches, researchers reported that unbalanced and inadequate nutritional habits affected athletes' performance negatively (Debnath et al, 2019). In summary, some endurance athletes -who have unhealthy nutritional habits such as skipping meals-may be at nutrient deficiency risk.…”
Section: Discussionmentioning
confidence: 99%